L2 control design of event-triggered networked control systems with quantizations. Issue 1 (January 2015) - Yan, Huaicheng; Yan, Sheng; Zhang, Hao; Shi, Hongbo
Abstract This paper deals with L2 controller design problem for event-triggered networked control systems (NCSs) with quantizations. The system state is periodically sampled and quantized. A new model of NCSs that involves the network conditions, state and event-triggered communication strategy is proposed. Based on this model, some novel criteria for the asymptotic stability analysis and L2 state feedback controller design method of the event-triggered NCSs with quantizations and time-varying delay are established to guarantee a prescribed L2 disturbance rejection attenuation level γ by using Lyapunov–Krasovskii function approach. Finally, a simulation example is provided to illustrate the effectiveness of the proposed method. It is shown that the average transmission interval could be increased substantially while the control performance is maintained.